The fiat money illusion: On the cost-efficiency of modern central banking - Karl-Friedrich Israel (The World Economy, 2021)
The traditional argument for unbacked fiat money stresses its potential benefits in terms of production costs. While there is an undeniable grain of truth in the traditional cost-saving argument, actual fiat money regimes around the world are belying it. The Eurosystem, the Bank of England, the Bank of Japan and the Federal Reserve System all operate under relatively high costs. In fact, their operating expenses exceed the estimated costs of a generic fractional-reserve gold standard. Even when the reserve ratio of the estimated gold standard is increased up to 100% on M1, the operating expenses of these modern central bank systems remain in a similar range. Hence, the cost-saving argument is illusory in these cases. These results suggest that a return to a money that is at least partially backed by gold might be more efficient even from the vantage point of the production costs of money. The Eurosystem and the Bank of Japan are particularly expensive institutions. Their annual operating expenses as a fraction of nominal GDP are more than twice as high as those of the Federal Reserve System and the Bank of England.
Keywords: 330; Bank of England; Bank of Japan; central bank; Eurosystem; Federal Reserve System; fiat standard; gold standard; operating expenses